Strategi Meningkatkan Kemampuan Membaca Siswa melalui Metode Silaba Kelas I Di SDN 24 Ampenan - Setiawati, Ayu; Nisa, Khairun; Thalhah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve the reading ability of first-grade students at SDN 24 Ampenan through the use of the syllabic method. The teacher’s role is crucial in enhancing students’ reading skills, especially in Grade 1, as these skills are essential for supporting learning activities in the classroom. One of the efforts undertaken is the use of an appropriate method to teach reading effectively. The syllabic method is applied as an approach to strengthening the reading abilities of first-grade students at SDN 24 Ampenan. This method has proven to be highly effective in guiding students to learn to read, as it helps them construct syllables more easily and supports their ability to form words. This research employed Classroom Action Research (CAR), with data collected through observation, interviews, and documentation. The implementation of the syllabic method successfully improved the reading ability of first-grade students at SDN 24 Ampenan, proceeded smoothly, and resulted in satisfactory outcomes.